2015
DOI: 10.2337/db15-0021
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Appears to Be Associated With Altered Muscle Protein Synthetic and Breakdown Responses to Increased Nutrient Delivery in Older Men, but Not Reduced Muscle Mass or Contractile Function

Abstract: Obesity is increasing, yet despite the necessity of maintaining muscle mass and function with age, the effect of obesity on muscle protein turnover in older adults remains unknown. Eleven obese (BMI 31.9 6 1.1 kg $ m 22) and 15 healthy-weight (BMI 23.4 6 0.3 kg $ m 22) older men (55-75 years old) participated in a study that determined muscle protein synthesis (MPS) and leg protein breakdown (LPB) under postabsorptive (hypoinsulinemic-euglycemic clamp) and postprandial (hyperinsulinemic hyperaminoacidemiceugly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
110
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(122 citation statements)
references
References 32 publications
9
110
3
Order By: Relevance
“…A recent study compared leg muscle protein metabolism in older obese and lean subjects under highly complex metabolic conditions of insulin, glucagon, and somatostatin administration and found similar indices of protein synthesis and breakdown and intramyocellular protein metabolic signaling in the two groups (19). The discrepancy with our results could relate to the metabolic complexity of the setup altering the concentrations of protein metabolic hormones such as insulin, glucagon, and growth hormone.…”
Section: Discussioncontrasting
confidence: 57%
“…A recent study compared leg muscle protein metabolism in older obese and lean subjects under highly complex metabolic conditions of insulin, glucagon, and somatostatin administration and found similar indices of protein synthesis and breakdown and intramyocellular protein metabolic signaling in the two groups (19). The discrepancy with our results could relate to the metabolic complexity of the setup altering the concentrations of protein metabolic hormones such as insulin, glucagon, and growth hormone.…”
Section: Discussioncontrasting
confidence: 57%
“…This finding, which necessitates replication, suggests that the maintenance of lean mass and strength may contribute to this obesity paradox, which suggests that obesity may provide a survival benefit under certain situations (Hainer and Aldhoon-Hainerova 2013). Our finding that the obese were associated with greater lean mass and strength is in agreement with previous research and is thought to be the result of the added mechanical work performed by the obese during activities of daily living (James et al 1978;Murton et al 2015). Although some have suggested that this obesity paradox is specific to men (Mohebi et al 2015;Migaj et al 2015), we observed no sex differences with this effect.…”
Section: Discussionsupporting
confidence: 90%
“…This analysis was modeled on a recent study that suggested that lean body mass and strength was not decreased in the obese compared to the healthy weight group, despite having a blunting of muscle protein synthesis in response to amino acids and a lower disposal of glucose (Murton et al 2015). One limitation noted by the authors was that they were unable to account for the influence of daily physical activity, although they noted that Bovert traits of muscle deconditioning were evident in the obese volunteers.^We provide epidemiological Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such anabolic resistance has not only been conjectured by us and others to contribute to the sarcopenia of ageing but it also appears to be a common feature of many kinds of muscle atrophy (e.g. with immobilization (Glover et al 2008), reduced physical activity (Breen et al 2013), heart failure (Toth et al 2010), obesity (Guillet et al 2009;Murton et al 2015) and cancer ), suggesting a final common pathway for a variety of insults resulting in diminished anabolism. Whereas the regulatory mechanisms of anabolic resistance remain poorly defined, possible links between reduced muscle MBF and diminished anabolic responses to plasma nutrient availability may be a general feature of a number of conditions.…”
Section: Discussionmentioning
confidence: 99%